Entropy generation and Joule heating applications for Darcy Forchheimer flow of Ree-Eyring nanofluid due to double rotating disks with artificial neural network - Faris Alzahrani; M. Ijaz Khan (Alexandria Engineering Journal, 2022)
This communication highlights the thermal characterization of Ree-Eyring fluid with entropy generation and nonlinear heat source/sink confined by double rotating disk. The classical significances of Joule heating and homogenous/heterogeneous chemical reactions are incorporated. The importance of porous medium is suggested by using the Darcy–Forchheimer expressions. Moreover, the slip effects are incorporated over double rotating disk. The problem is formulated in terms of differential expressions. The analytical procedure is adopted via homotopic procedure. The accuracy of results is confirmed. Moreover, a optimized model for Artificial neural network (ANN) is developed as a novelty. The insight dynamic of physical parameters is assessed with aims of several graphs. The entropy generation pattern and evaluation of Bejan number is predicted due to flow parameters. The graphical simulations worked out form current model reveal that the entropy generation rate improves with Weissenberg number as well as slip factor. The presence of higher order slip is also effective to enhance the Bejan number.